A Famous Chinese Medicine Formula: Yinhuo Decoction Antagonizes the Damage of Corticosterone to PC12 Cells and Improves Depression by Regulating the SIRT1/PGC-1α Pathway. (4th March 2022) - Xu, Hongdan; Xing, Shurong; Lei, Xia; Yi, Jinyue; Liu, Shuang; Du, Yanqiu; Yang, Bo; Zhang, Ning
Abstract : The study aimed to explore the antidepressant effect of Yinhuo Decoction and further to explore its underlying molecular mechanism acting on depressant. Here, high-performance liquid chromatography (HPLC) analysis was used to the composition analysis. Postmenopausal depression (PMD) model and corticosterone (CORT)-induced cell model were constructed. Adrenal coefficient and hematoxylin and eosin staining were applied to assess changes in the adrenal glands. MTT staining, Hoechst 33342 staining, and JC-1 fluorescence staining were used to detect the PC12 activity and apoptosis. CORT and oxidative stress indicators were measured using commercial kits. Western blot and immunohistochemical were used to detect the protein expression of GCR. In addition, genes related to SIRT1/PGC-1 α pathway were also tested. In PMD model mice, Yinhuo Decoction evidently increased adrenal coefficient and relieved adrenal lesions. Meanwhile, we observed that Yinhuo Decoction reduced the CORT and GCR levels. In CORT-treated PC12 cells, Yinhuo Decoction remarkably reduced cytotoxicity and apoptosis. Besides, Yinhuo Decoction attenuated the oxidative stress response. Mechanically, we confirmed that Yinhuo Decoction reduced CORT-induced PC12 damage by regulating SIRT1/PGC-1 α pathway. Thus, we concluded that Yinhuo Decoction antagonized CORT-induced injury in PC12 cells and improved depression in PMD mice. This provided a new direction for the treatment of depression.